2020
DOI: 10.3390/polym12030652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Structure and Degree of Branching on the Stability of Proton Exchange Membranes Based on Sulfonated Polynaphthylimides

Abstract: Hydrolytic stability and oxidative stability are the core properties of sulfonated polynaphthylimides (SPIs) as proton exchange membranes. The chemical structure of SPIs directly influences the performance. Herein, three different series of branched SPIs were designed and prepared using 1,3,5-tris (2-trifluoromethyl-4-aminophenoxy) benzene as a trifunctional monomer and three non-sulfonated diamine monomers, such as 4,4′-oxydianiline (ODA), 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (6FODA), and 4,4′-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Before blistering, the proton conductivity of all the membranes rises with the temperature increased in the range of 30 °C to 90 °C. This temperature dependent proton conductivity has been also reported by other research groups [ 30 ]. The proton conductivity of all membranes sharply dropped after the pressure-loaded blistering, particularly for the non-reinforced membrane (Nafion 211), presumably due to the morphological changes such as the rearrangement or the deformation of the ionic channels [ 31 ].…”
Section: Resultssupporting
confidence: 88%
“…Before blistering, the proton conductivity of all the membranes rises with the temperature increased in the range of 30 °C to 90 °C. This temperature dependent proton conductivity has been also reported by other research groups [ 30 ]. The proton conductivity of all membranes sharply dropped after the pressure-loaded blistering, particularly for the non-reinforced membrane (Nafion 211), presumably due to the morphological changes such as the rearrangement or the deformation of the ionic channels [ 31 ].…”
Section: Resultssupporting
confidence: 88%
“…In addition to the abovementioned parameters, other factors such as membrane morphology and water uptake are of great importance. Although high water uptake improves proton conductivity, excessive absorbed water can deteriorate the membrane's mechanical strength, chemical stability, and dimensional stability due to the weakened hydrogen bonding interactions and Van der Waals forces caused by polymer swelling [35,87]. It has been reported that the tensile strength of the membrane decreases by about 25-30% with the addition of 10% water [88].…”
Section: Other Important Parametersmentioning
confidence: 99%
“…14 On the other hand, the aliphatic and ether bonds added as electron-donating groups are vulnerable to attacks from free radicals like hydroxyl groups, leading to a decrease in the stability of the oxidation process. 15,16 Hence, it is necessary for weigh oxidation stability and hydrolytic stability to prepare better PI films.…”
Section: Introductionmentioning
confidence: 99%